2018
DOI: 10.4102/sajce.v8i1.546
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on phonological processing and reading development in Northern Sotho children learning to read in English: A case study of Grade 3 learners

Abstract: Gender differences in reading development are a global phenomenon, with girls typically performing better than boys. Some studies have reported gender differences favouring girls in reading comprehension in South Africa, but little systematic evidence exists about gender differences in the cognitive-linguistic abilities that underlie reading development. This study investigated the effect of gender on phonological processing and reading development in Northern Sotho–English bilingual children. Grade 3 learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The data might be helpful in addressing reading problems that are likely to occur among Malaysian learners, namely, lacking of PA [36], and enhancing and strengthening the English language learning in Malaysia, regardless of geographical and demographical factors. The data obtained from the tests were considered greatly important in assisting teachers to come up with strategic schemata in to overcome early problems in reading because PA is fundamental to later reading [4,30,31,40]. The findings from this data were able to contribute to the empirical literature on PA progress among young ESL learners in Malaysia because PA is considered new to this setting [43].…”
Section: Discussionmentioning
confidence: 91%
“…The data might be helpful in addressing reading problems that are likely to occur among Malaysian learners, namely, lacking of PA [36], and enhancing and strengthening the English language learning in Malaysia, regardless of geographical and demographical factors. The data obtained from the tests were considered greatly important in assisting teachers to come up with strategic schemata in to overcome early problems in reading because PA is fundamental to later reading [4,30,31,40]. The findings from this data were able to contribute to the empirical literature on PA progress among young ESL learners in Malaysia because PA is considered new to this setting [43].…”
Section: Discussionmentioning
confidence: 91%
“…When observing the content of the items identified as statistically different (Table 5), there appears to be no obvious gender discrimination. The literature on gender differences relating to cognitive assessment suggests that women are more skilled at verbal tasks than men (Griskevica & Rascevska, 2009;Hur et al, 2017;Hyde, 1981;Miller & Halpern, 2014;Palejwala & Fine, 2015;Strand et al, 2006;Toivainen et al, 2017;Wai et al, 2018;Wilsenach & Makaure, 2018), but this finding cannot be concluded in respect of the ECT on the basis of three statistically different items.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…Despite these diverse views on gender differences in cognitive assessment across numerous studies in American, European and Asian countries, in Africa very few studies have been conducted on differences in cognitive abilities between men and women (Hur et al, 2017). A recent study on differences in cognitive assessment in South Africa, however, noted a disconcerting trend amongst Grade 3 boys in this country, because they were consistently achieving much lower scores compared with women in Grade 3 (Wilsenach & Makaure, 2018). Another study conducted by Bakhiet and Lynn (2015) using the Ravens Coloured Progressive Matrices (a non-verbal intelligence assessment) on Xhosa South African schoolchildren found that the intelligence scores of these schoolchildren were similar to Zulu South African schoolchildren who had performed the same test some years before.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations